Muslim and Hindu Marriage Laws in Bangladesh A Comparative Study | বাংলাদেশে মুসলিম এবং হিন্দু বিবাহ আইন : একটি তুলনামুলক আলোচনা (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
In Bangladesh there are 88 percent Muslims and the remaining are Hindus, Christians and Buddhists respectively. As a social and legal institution, marriage is a recognized in every Society and by every faith. Directed by the different religious rules and regulations, the marriage laws are unique to each other. In this article, the only motive that has been indicated is to compare or distinguish the Muslim marriage Law and Hindu marriage Law. It will focus on the major differences and impacts upon the marital relationships. The significance of the laws also be discussed. Side by side the security and rights of women is also mentioned here. It has also been proven that the concept of women rights is in fact originated from Islamic jurisprudence although there are many debates and arguments on this issue. This study is based on the primary and secondary sources with regard to the Muslim and Hindu marriage laws. Form the study the readers will be able to have a clear idea on the issue. It is to be noted that the method of description and comparative study of the topic mentioned has been analyzed in this text.